Agricultural Agglomeration Strategy in Supporting Regeneration of Shallots Farmers on Marginal Land - Rustami, Rustami; Dahlia, Ira; Febriani, Restina; Mawartya, Salma; Ramadhani, Titis B.; Widhiningsih, Diah Fitria (JSEP (Journal of Social and Agricultural Economics), 2024)
The declining interest of the younger generation to become farmers has implications for the crisis of farmer regeneration, which results in a decline in state income and increased import dependence. On the other hand, there is agglomerated marginal land farming in Srigading Village, Sanden Sub-district, Bantul which has increased agricultural yields in 2022. This research discusses the factors supporting and inhibiting the level of farmer regeneration to analyze the determinants of the success of agricultural agglomeration. This research was conducted in Srigading Village, Sanden District, Bantul Regency. This study used a qualitative approach with primary data from interviews with young farmers aged 20-35, old farmers aged over 35, non-farmers, extension workers, and government agencies to identify supporting and inhibiting factors for farmer regeneration. Furthermore, this research uses a case study and ecological-geographical approach, testing the validity of the data using the source triangulation method. The results show that aspects such as self, family, friends, government, social, social media, economy, and organization are both supporting and inhibiting factors for the level of agricultural regeneration, while aspects such as school and geography are neutral factors. Based on the interview results, agglomerated agricultural conditions facilitate access to knowledge, distribution of government assistance, and encourage innovation to develop agriculture. Spatial aspects such as distance between fields, exchange of information flows between farmers, collective use of resources, and government policies are determinants of the success of agglomeration strategies in supporting farmer regeneration.